Utdanning for bærekraft Erfaring og forskning fra barnehage og skole - Bredal-Tomren, Tom Sverre (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
In 2020, Norway's national curriculum for primary and secondary school eduction, known as Kunnskapsløftet, came into effect. The plan is marked by increased emphasis on education for sustainability, and a notable example of this is the inclusion of sustainable development as an interdisciplinary topic in most subjects in primary and secondary school. As a result, the focus on sustainabilty has also increased in teacher eduction programs, for preschool as well as primary and secondary school teachers. Furthermore, a number of research networks have been established to explore sustainability in the context of education, and new research and textbooks are being published on this topic. This anthology presents new research on how the subject of sustainability is being handled in schools and preschools today, to all those interested in the topic. Education for Sustainability. Experience and Research from Preschool, Primary and Secondary School can be read as a handbook in sustainable teacher and preschool teacher education, or as a collection of individual research articles that contribute to greater awareness of, focus on and commitment to education for sustainability.